Efecto de cinco dosis crecientes de solución “A” en el rendimiento de Cucumis sativus L. VARIEDAD MARKETMORE en Sustrato Hidropónico en Trujillo-La Libertad - Valdiviezo Ponce, Danny Johnatan (2017)
This research was conducted in hydroponics module of the National University of Trujillo, in order to determine the effect of five increasing doses of nutrient solution in Cucumis sativus L. yield variety Marketmore in hydroponic substrate. the randomized complete design (RCBD) with four replications and five treatments used blocks. The study treatments were T1 (increasing dose 1 of nutrient solution A), T2 (increasing dose 2 of nutrient solution A), T3 (increasing dose 3 of nutrient solution A), T4 (increasing dose 4 of nutrient solution A), T5 (increasing doses 5 of nutrient solution A). After installing the experiment conduction cultivation began applying their respective treatment to each increasing dose, then when the plant reached flowering evaluating the various parameters under study began to plant senescence. As a result it was determined that the treatment T5 reached the highest performance with 172.62 t.ha-1 and treatment T1 with 97.95 t.ha-1 being the lowest, concluding that the cultivation Gherkin responded with a minimal difference to low doses fertilization (T1: T2). but better he responded to the average doses (T4: T3) presenting increased production with fertilization (T5) as well as the largest number of fruits.